1990
DOI: 10.1104/pp.94.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Chlorsulfuron Modifies Biosynthesis of Acyl Acid Substituents of Sucrose Esters Secreted by Tobacco Trichomes

Abstract: Sucrose esters and duvatrienediol diterpenes are principal constituents formed in and secreted outside head cells of trichomes occurring on surfaces of Nicotiana tabacum. Using trichome-bearing epidermal peels prepared from midveins of N. tabacum cv T.l. 1068 leaves, we found that chlorsulfuron reduced and modified radiolabeling of sucrose ester acyl acids derived from branched-chain amino acid metabolism. The herbicide did not effect formation and exudation of diterpenes which are products of isoprenoid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The biosynthesis of acyl sugars is relatively poorly understood. Feeding studies demonstrated the involvement of branched chain amino acid pathway intermediates as a source of branched acyl chains ( Figure 7 ) ( Kandra and Wagner, 1990 ; Walters and Steffens, 1990 ). Previously published results are consistent with the hypothesis that these short acyl chains are then elongated to produce the variety of chain lengths observed in tomato acyl sugars ( van der Hoeven and Steffens, 2000 ; Kroumova and Wagner, 2003 ; Slocombe et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of acyl sugars is relatively poorly understood. Feeding studies demonstrated the involvement of branched chain amino acid pathway intermediates as a source of branched acyl chains ( Figure 7 ) ( Kandra and Wagner, 1990 ; Walters and Steffens, 1990 ). Previously published results are consistent with the hypothesis that these short acyl chains are then elongated to produce the variety of chain lengths observed in tomato acyl sugars ( van der Hoeven and Steffens, 2000 ; Kroumova and Wagner, 2003 ; Slocombe et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mature gland cells, pathways for synthesis of valine, leucine, and isoleucine appear to be diverted to form CoA-activated acids for esterification in sucrose ester formation. We have suggested that normal flow of carbon to amino acids is diverted somewhat in mature glands due to the lack of a sink for branched-chain amino acid (lack of protein synthesis) or a lack of transaminase to convert ketoacid intermediates to amino acids (14,15 (4,20). Clearly, further study is needed to define the metabolic capability of secreting gland cells but one can already begin to consider modification of isoprenoid metabolism, reactions which modify terpene skeletons, and branched-chain amino acid metabolism (in sugar ester producers) to alter exudate chemistry.…”
Section: Is Exudate Accumulation Capacity Related To the Structure Ofmentioning
confidence: 99%
“…Lines under atoms of carbon skeletons at top indicate the position of label derived from [2-14C]acetate. The metabolic sequences from pyruvate through valeryl-CoA, methylbutyryl-CoA, and 3-methylvaleryl-CoA were concluded from previous work (6,7). Superscripted letters represent principal sugar ester alkyl groups formed (and labeled from [2-14C]acetate, shown here) in trichome glands of tomato (T), petunia (P), and Nicotiana glutinosa (G).…”
mentioning
confidence: 99%
“…In contrast, metabolism leading to the biosynthesis of mcFAs is not well understood (4,5), particularly that catalyzing the formation of branched and odd-length mcFAs. Straight, iso-, and antiso-branched, oddand even-length scFAs are synthesized via modified branched-chain amino acid (bcAA) metabolism in tobacco trichome glands (6,7). It is possible that at least branched and odd-length mcFAs are formed in this tissue similarly.…”
mentioning
confidence: 99%
See 1 more Smart Citation